2009
DOI: 10.1038/bmt.2009.203
|View full text |Cite
|
Sign up to set email alerts
|

Utility of early versus late fiberoptic bronchoscopy in the evaluation of new pulmonary infiltrates following hematopoietic stem cell transplantation

Abstract: Pulmonary infiltrates frequently complicate hematopoietic SCT (HSCT). The utility of fiberoptic bronchoscopy (FOB) with bronchoalveolar lavage (BAL) in the evaluation of new pulmonary infiltrates, particularly as it relates to optimal timing of the procedure, is unclear. Based on this, we retrospectively reviewed 501 consecutive, adult, nonintubated patients who underwent 598 BALs for evaluation of new pulmonary infiltrates during the first 100 days following HSCT to determine whether diagnostic yields for inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
146
4
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(170 citation statements)
references
References 33 publications
10
146
4
10
Order By: Relevance
“…Being an abundant component of inhaled air, these organisms represent one of the leading causes of IFI-related morbidity and mortality (1)(2)(3)(4)(5). Due to the crude mortality of 80 to 90% in the absence of adequate treatment, timely diagnosis and early start of antifungal therapy are key factors in the successful treatment of IPA, as delayed antifungal therapy has a negative impact on the survival of these patients (6). Various studies have shown that early diagnosis and initiation of antifungal therapy may improve IFI survival to Ͼ80% (7)(8)(9).…”
mentioning
confidence: 99%
“…Being an abundant component of inhaled air, these organisms represent one of the leading causes of IFI-related morbidity and mortality (1)(2)(3)(4)(5). Due to the crude mortality of 80 to 90% in the absence of adequate treatment, timely diagnosis and early start of antifungal therapy are key factors in the successful treatment of IPA, as delayed antifungal therapy has a negative impact on the survival of these patients (6). Various studies have shown that early diagnosis and initiation of antifungal therapy may improve IFI survival to Ͼ80% (7)(8)(9).…”
mentioning
confidence: 99%
“…This was similar to the finding reported by Shannon who had a 32% yield in patients with an ANC <100 and a 50% yield in patients with an ANC <500. 10 Mechanically ventilated patients had a higher BAL yield. This may be a reflection of the small sample size or severity of illness.…”
Section: Resultsmentioning
confidence: 99%
“…This correlates with Shannon's findings of an improved BAL sensitivity in early versus late BAL in a similar population. 10 Interestingly, among patients already on antimicrobial therapy for >48h at the time of BAL, a change in the regimen during the 48h preceding BAL was associated with a better yield. This may be a reflection of sample size, a new infection, inappropriate antimicrobial change, severity of illness, or less likely colonization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the >48 h delay reported between time of referral time of procedure in 40% of hospitals is considered suboptimal; yield from BAL is highest when performed within 24 h of new infiltrates and declines significantly by 5 days. 19 Inclusion of respiratory physicians within the multidisciplinary team providing care for these patients should be encouraged. In contrast, non-culture-based tests and TDM were generally available off-site.…”
mentioning
confidence: 99%